(untitled) (The Harvest, 2026)
The advent of artificial intelligence (AI) constituted skepticism including ethical dilemma, social inclusion, and bias along with its opportunities. While it is crawling to cultivate in its early stages, the stakeholders of all levels have concerns about the impact that it would bring in the future. Simultaneously, organizations and individuals are utilizing it for several automated tasks despite criticism and rumors in online platforms. As a matter of fact, the conventional ICT digitalized modern business. However, there still remained several business bottlenecks due to insufficient automated instrumentation, information overload, and delayed decision-making. The business process was eased but not satisfyingly handled as numbers of employees were still needed to accomplish the performance. There were various sectors which were impacted with suboptimal productivity, and poor services in the absence of right instrumentation. The objective of this study is to explore outweighing factors of AIdriven systems over the prevailing skepticism and rumors. This study’s thematic approach to analyses the secondary data. A total of 105 articles were analyzed in this research. This analysis focused on the studies published from 2020 to 2025. The analysis was emphasized around two key areas: contribution and opportunity. This study found that AI powered systems revolutionized the business today in comparison to conventional digitalization. Efficiency in decision making and operation of business have been improved. Chatbot assisted in various communications of business. The AI system saved time on scheduling new candidates in the HR department.